2001
DOI: 10.1054/bjoc.2000.1598
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of the predominant Jewish mutations in BRCA1 and BRCA2 in unselected Ashkenazi colorectal cancer patients

Abstract: It is presently unclear whether carriers of BRCA1 mutations have an increased risk for colorectal cancer (CRC). To gain insight into this issue, 225 unselected Ashkenazi Jewish CRC patients were tested for the presence of the three common Jewish BRCA1/2 germline mutations: 185delAG and 5382insC ( BRCA1 ) and 6174delT ( BRCA2 ). A total of four carriers was found (4/225, 1.78%). This frequency is similar to the estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The three founder mutations, BRCA1 187delAG, BRCA1 5385insC and BRCA2 617delT, have a combined prevalence exceeding 2 per cent in Ashkenazi Jews, so most research has been conducted in this population. The results of several studies concur with the present finding that BRCA1 and BRCA2 mutation carriers in this population do not have a higher than normal incidence of colorectal cancer. Mersch and colleagues studied the cancer risk associated with BRCA1 and BRCA2 mutations among the general population.…”
Section: Discussionsupporting
confidence: 91%
“…The three founder mutations, BRCA1 187delAG, BRCA1 5385insC and BRCA2 617delT, have a combined prevalence exceeding 2 per cent in Ashkenazi Jews, so most research has been conducted in this population. The results of several studies concur with the present finding that BRCA1 and BRCA2 mutation carriers in this population do not have a higher than normal incidence of colorectal cancer. Mersch and colleagues studied the cancer risk associated with BRCA1 and BRCA2 mutations among the general population.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of BRCA1 / 2 mutations in the general US population is estimated to be approximately 1 in 300–500 . In order to identify enough carriers for an accurate estimation of risk, most case–control studies have been restricted to populations where the prevalence is increased, such as Ashkenazi Jews and Poland . Results from specific populations with founder mutations cannot necessarily be generalized to the entire carrier population; if the risk of colon cancer differs for different mutations, then the results may not be generalizable to carriers of other mutations.…”
Section: What Is the Penetrance Of Brca1/2 Mutations For Colorectal Cmentioning
confidence: 99%
“…The approaches used in these studies included prospective cohort, retrospective cohort and kin‐cohort designs (summarized in Table ), association/case–control designs (Table ), and family‐based designs (Table ). In general, most of the positive results (relative risks of two to four) were derived from studies of high‐risk cancer families, whereas studies of unselected colon cancer patients generally found no significantly increased risks for either BRCA1 or BRCA2 . The validity of these studies must be assessed for precision and statistical power, which is determined in large part by the number of exposed cases identified (colon cases with mutations), and for bias, in order for conclusions to be made.…”
Section: What Is the Penetrance Of Brca1/2 Mutations For Colorectal Cmentioning
confidence: 99%
“…These authors argued that the higher incidence of colon cancer observed in some BRCA1 families may be attributed, at least in part, to misdiagnosed ovarian and rectal cancer [17]. Formal analysis showed no increased predisposition to colorectal cancer in BRCA1 mutation carriers [18].…”
Section: Inter-study Risk Variabilitymentioning
confidence: 99%